Brief inhalation of nitric oxide increases resuscitation success and improves 7-day-survival after cardiac arrest in rats: a randomized controlled animal study. Issue 1 (December 2015) - Brücken, Anne; Derwall, Matthias; Bleilevens, Christian; Stoppe, Christian; Götzenich, Andreas; Gaisa, Nadine; Weis, Joachim; Nolte, Kay; Rossaint, Rolf; Ichinose, Fumito; Fries, Michael
Abstract Introduction Inhaled nitric oxide (iNO) improves outcomes when given post systemic ischemia/reperfusion injury. iNO given during cardiopulmonary resuscitation (CPR) may therefore improve return of spontaneous circulation (ROSC) rates and functional outcome after cardiac arrest (CA). Methods Thirty male Sprague-Dawley rats were subjected to 10 minutes of CA and at least 3 minutes of CPR. Animals were randomized to receive either 0 (n = 10, Control), 20 (n = 10, 20 ppm), or 40 (n = 10, 40 ppm) ppm iNO during CPR until 30 minutes after ROSC. A neurological deficit score was assessed daily for seven days following the experiment. On day 7, brains, hearts, and blood were sampled for histological and biochemical evaluation. Results During CPR, 20 ppm iNO significantly increased diastolic arterial pressure (Control: 57 ± 5.04 mmHg; 20 ppm: 71.57 ± 57.3 mmHg, p < 0.046) and decreased time to ROSC (Control: 842 ± 21 s; 20 ppm: 792 ± 5 s, (p = 0.02)). Thirty minutes following ROSC, 20 ppm iNO resulted in an increase in mean arterial pressure (Control: 83 ± 4 mmHg; 20 ppm: 98 ± 4 mmHg, p = 0.035), a less pronounced rise in lactate and inflammatory cytokine levels, and attenuated cardiac damage. Inhalation of NO at 20 ppm improved neurological outcomes in rats 2 to 7 days after CA and CPR. This translated into increases in 7 day survival (Control: 4; 20 ppm: 10; 40 ppm 6, (p ≤ 0.05 20 ppm vs Control and 40 ppm). Conclusions Our study revealed that breathing NO during CPR markedly improved resuscitation success, 7-day neurological outcomes and survival in a rat model of VF-induced cardiac arrest and CPR. These results support the beneficial effects of NO inhalation after cardiac arrest and CPR.